Rancang Bangun Alat Pemotong Ikan Patin Otomatis untuk Bahan Baku Ikan Salai - Edilla Edilla; Rudi Fesri; Made Rahmawaty; Hendriko Hendriko (JURNAL INTEGRASI, 2021)
Catfish (Pangasius sp) is a type of fish that is widely used as raw material for processed smoked fish. Salai fish is one of the local culinary delights that are processed by cutting / splitting as well as drying and curing (smoking) which takes approximately 1-2 days and is one of the most familiar culinary delights in Indonesia, especially in Riau Province. However, in making this processed smoked fish, the process of cutting / splitting the fish is still done manually. This can be overcome by means of automatic feeder and catfish cutter. The way this tool works is that fresh fish will be put manually on the conveyor belt then the fish will go to the fish cutting process using a rotating circular blade and will cut the fish according to the depth has been adjusted for the raw material for processed catfish smoked fish. From data collection using 20 fish with a weight ranging from 150 to 365 grams and a length of fish ranging from 23 - 35 cm, the average working time of the 20 fish is 2,27 seconds. To determine the capacity of the tool, a continuous cutting process of 5 fish was carried out and the resulting time was 6,02 seconds, so in 1 minute this tool was able to process catfish as much as 48-49 fish per minute.